Design and Development of a Fuzzy Logic-Based Temperature and Humidity Control System for Cricket Breeding Enclosures - Hamala, Nanda Rizky; Sumadi (Emitor: Jurnal Teknik Elektro, 2024)
Cicadas are insects that can be cultivated in Indonesia. The most common species of cicadas cultivated in Indonesia are Gryllus bimaculatus and Acheta domesticus. Cicadas are commonly used as livestock feed, including ornamental chickens, poultry, and birds, because of their high protein content. Cicadas cultivation in Indonesia is still mostly done manually, both in the process of controlling the environmental conditions around the cage and in the process of breeding cicadas eggs. One of the problems that often occurs is the temperature and humidity in the cicadas cage are not stable. Therefore, this research aims to design a system that can control the temperature and humidity in the cicadas cage. This system applies the fuzzy logic method to control actuators that can regulate the duration of spraying and the level of lighting needed in the cicadas cage based on the fuzzy rules that have been made. The components used in this system include Arduino uno, DHT22 sensor, relay, AC light dimmer, mist maker, lamp, and fan. The results of this research show that the temperature and humidity control system in a cicadas cage using fuzzy logic method with a predetermined setpoint has been realized. The accuracy testing of the DHT22 sensor obtained an error of 1.55% and a temperature accuracy rate of 98.44% and humidity of 1.66% with an accuracy rate of 97.64%. Then, the testing of the comparison results on the system and fuzzy simulation with the matlab application obtained an accuracy percentage in the mist maker testing of 97.37% and in the lamp testing of 98.81%.